2011
DOI: 10.5152/akd.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left and right ventricular pulsed and tissue Doppler myocardial performance index values using Z-score in newborns with hypoxic-ischemic encephalopathy

Abstract: ÖZETAmaç: Çalışmanın amacı; hipoksik iskemik ensefalopatili (HİE) ve sağlıklı term yenidoğan bebeklerde, kardiyak etkilenmeyi göstermek amacı ile pulsed (PD) ve doku Doppler (DD) tekniklerini kullanarak miyokart performans indeksini (MPİ/Tei indeksi) belirlemek ve bu iki teknik sonuçları arasında ortaya çıkan farklılıkları değerlendirmektir. Yöntemler: Çalışma prospektif gözlemsel bir çalışmadır. Postnatal ilk 24 saat içinde belirlenen kriterlere göre perinatal asfiksi tanısı konulan 20 term yenidoğan ve kontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Neonatal hypoxic‐ischemic encephalopathy (HIE) is a clinically defined neurological condition with deficiency of oxygen, while the HIE often associated with cardiac dysfunction in term infants (Liu X, et al, 2011). And The degree of cardiac response in neonates with HIE is associated with the severity of hypoxia (Alp H, et al, 2011). Correlational research reported for the first time that acute cerebral ischemia significantly increased left ventricular end diastolic pressure (LVEDP), but decreased left ventricular systolic pressure (LVSP), which indicate that acute cerebral ischemia may specifically disturb cardiac function and calcium homeostasis, subsequently leading to Ca 2+ overload and myocardial dysfunction (Sun L, et al, 2010).…”
Section: Bcl‐2 Cerebral Ischemia and Myocardial Ischemiamentioning
confidence: 99%
“…Neonatal hypoxic‐ischemic encephalopathy (HIE) is a clinically defined neurological condition with deficiency of oxygen, while the HIE often associated with cardiac dysfunction in term infants (Liu X, et al, 2011). And The degree of cardiac response in neonates with HIE is associated with the severity of hypoxia (Alp H, et al, 2011). Correlational research reported for the first time that acute cerebral ischemia significantly increased left ventricular end diastolic pressure (LVEDP), but decreased left ventricular systolic pressure (LVSP), which indicate that acute cerebral ischemia may specifically disturb cardiac function and calcium homeostasis, subsequently leading to Ca 2+ overload and myocardial dysfunction (Sun L, et al, 2010).…”
Section: Bcl‐2 Cerebral Ischemia and Myocardial Ischemiamentioning
confidence: 99%